1994
DOI: 10.1159/000172264
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of Acute Necrotizing Pancreatitis with Open Packing

Abstract: From March 1, 1991 to December 31, 1994, a total of 76 patients with acute pancreatitis were treated at the surgery division. Out of these, 16 (21%) were treated for necrotizing pancreatitis with open packing and programmed lavage. They were 12 men and 4 women with an average age of 51.5 years. The Ranson score on admission averaged 5.6. The total duration of hospitalization was 58.25 days, the average stay in the intensive care unit 23.7 days. In 6 (37.5%) patients, there were serious surgical complications: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The aim of surgery for infected pancreatic necrosis is to eliminate the intraperipancreatic necrotic tissue and preserve viable pancreas to the maximum possible extent 8 to avoid exocrine and/or endocrine pancreatic insufficiency as well as hemorrhage. However, severe acute pancreatitis is a dynamic process that continues to evolve, which means that areas of necrosis may extend over ensuing days.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of surgery for infected pancreatic necrosis is to eliminate the intraperipancreatic necrotic tissue and preserve viable pancreas to the maximum possible extent 8 to avoid exocrine and/or endocrine pancreatic insufficiency as well as hemorrhage. However, severe acute pancreatitis is a dynamic process that continues to evolve, which means that areas of necrosis may extend over ensuing days.…”
Section: Discussionmentioning
confidence: 99%
“…The combination between this technique with the drainage of the lesser sac, the drainage of the main collections developed in retroperitoneal subphrenic left region or submesocolic region and the drainage of the Douglas, makes the OPLS technique a good surgical option in selected cases, despite the repeated trauma (relative) on tissues at this level. The principles underlying the OPLS technique are [12,15,16]: it facilitates the re-exploration of the lesser sac to the next scheduled inspection; allows an effective drainage of intra abdominal sepsis (surprising formation of new collections to be drained); and virtually eliminates the risk of developing abdominal compartment syndrome (ACS) [10,17].…”
Section: Discussionmentioning
confidence: 99%
“…17 The transperitoneal approach enables physicians to perform necrosectomy, place tubes for lavage drainage, and access the gallbladder and bile duct if the cause is lithiasis, but it involves major morbidity and mortality and a high rate of repeated surgery for abdominal sepsis. 1,3,15,[18][19][20][21] Various possibilities have been suggested: necrosectomy plus lavage, with lower morbidity and mortality rates but more repeated surgeries for sepsis, and necrosectomy associated with periodic debridements, with similar mortality and greater local morbidity rates. 3 After transperitoneal access and in the presence of clinical signs of sepsis but without collections in the CT scan, recent studies 11,22 have suggested dilation of the drainage orifice to insert a flexible endoscope for lavage and aspiration of the infected necrosis, which carries morbidity of 25% and no mortality.…”
Section: Commentmentioning
confidence: 99%
“…1,3,15,[18][19][20][21][22][23] With purely retroperitoneal access, mortality ranges from 0% to 33%, morbidity is lower (20%-62%), and the number of repeated surgeries per patient averages 0 to 3.6 ( Table 2). [5][6][7][8][9]12 …”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation